Anonim, Hermetica Vindobonensia I-IV - Sowińska, Agata (Vox Patrum, 2023)
The Vienna Hermetica consist of four fragmentally preserved texts found on Viennese papyri (Papyri Vindobonenses Graecae 29456r et 29828r) from the 2nd or 3rd century AD. Fragments III and IV are almost completely missing. On the other hand, the content of Hermetica Vindobonensia I and II oscillates around the privileged position of man (HV I) and the only nameless God (HV II).